Evaluation of the Thoracic Aortic Dissection Treated by Endografts Covering a Longer Distance of Aorta According to the Location of the Adamkiewicz Artery - Yingbin, Jia; Jiefei, Ma; Jian, Li; Yonghui, Su; Haiyan, Pan; Baimeng, Zhang; Weigoo, Fu (The Thoracic and Cardiovascular Surgeon, 2013)
Background Presurgical locating the Adamkiewicz artery (AKA) will be very helpful for thoracic aortic endovascular repair. This study aimed to evaluate the effects of using longer endografts according to location of AKA on outcomes of endovascular treatment for thoracic aortic dissection.Methods A total of 217 patients (143 men, 74 women; mean age: 65 ± 11 years) with type B dissection were divided into two groups according to whether the AKA was identified or not presurgically. Endovascular repairs were performed for all patients. Distal landing levels of endograft were recorded. The thrombosis of false lumen and the complications of spinal cord ischemia and endoleak were analyzed.Results The AKA was detected in 121 (55.8%) patients (group A) and not detected in 96 (44.2%) patients (group B). According to the levels of AKA, patients in group A obtained the stabilization of the affected thoracic aorta over a longer distance. The ratio of patients with distal landing levels at T8–T10 was significantly higher than in group B (59.5 vs. 12.5%, χ2 = 49.85, p < 0.01). Also, during the follow-up to 7.3 months, the ratio of patients with total thrombosis of false lumen in group A was significantly higher than group B (32.1 vs. 19.1%, χ2 = 4.34, p = 0.037).Conclusions Accurate preoperative knowledge of AKA is extremely useful for selecting a longer device to provide a better structural stability of affected aorta and promote false lumen thrombosis during a midterm follow-up phase.
Keywords: artery of Adamkiewicz; thoracic aortic dissection; thoracic endovascular repair